Flourishing in adaptive community: balancing structures and flexibilities. Issue 2 (13th March 2018) - Cherkowski, Sabre; Hanson, Kelly; Walker, Keith
Abstract : Purpose: This paper documents findings from a qualitative research project on flourishing in schools using a positive organizational research approach. The purpose of this paper is to uncover and bring to description educators' experiences of the conditions, forces and influencing factors for flourishing in their context. The main objectives were to inform research and practice in school improvement from a positive perspective, provide knowledge and practice about noticing and growing well-being for educators and to encourage an attention on individual and collective well-being as an organizational imperative. Design/methodology/approach: To gain a rich description of what it means for educators to feel a sense of flourishing in their work, the researchers used qualitative, case study methods and appreciative research activities. For the case study reported on in this paper, data were collected through open-ended, appreciative, focus group conversations and researcher observations in the participants' classrooms. Conversations were recorded and transcribed. The researchers analyzed the transcripts using an iterative process of coding, categorizing and abstracting data. Findings: Participants grew their adaptive communities through balancing structures (collaboration, purpose, administrator support) with flexibilities (synergy, creativity, tinkering, friendships) for adaptation and co-creation. Well-being was connected with feeling collegial support, care, shared meaning and engagement and where positive relationships were central in their work. These relational conditions seemed to contribute to building a social container that promoted flourishing. This led to innovation as teachers worked together in ways that promoted their learning and growth as a group, and increased their sense of vitality in their work. The researchers found that the principal plays a vital role in fostering, encouraging and sustaining conditions for teachers to cultivate adaptive community. Research limitations/implications: While small in scale and not generalizable across contexts, this research offers particular examples of what is working well for these teachers. Insights from these examples are intended to be generative, potentially resonating with and inspiring others to examine the possible benefits and potentials that may come from a positive approach to research and practice in school improvement in their own contexts. Engaging in positive organizational research in schools led to new insights on the work of teaching, learning and leading in schools. The researchers suggest that this positive, appreciative and generative perspective offers potentials and benefits for new understandings on school improvement. Practical implications: The findings from this case study indicate that more attention is needed to supporting educators to cultivate the conditions necessary to experience rich and meaningful relationships within which they will thrive, grow and innovate in their teaching. At a system level, the authors argue for a re-orientation of schools toward well-being and a more holistic and human-development perspective on schooling. Social implications: Currently and internationally, schooling is under re-design as the authors learn more about the need to organize the schools in ways that encourage the kinds of teaching and learning necessary to prepare young people for an increasingly unpredictable future. The findings from this study highlight the importance of attending to teacher well-being as a fundamental aspect of encouraging the kind of teaching needed for the kinds of learning desired in schools across all contexts. Originality/value: This case study provides the findings that illustrate the potential and benefits of research on school organizations from a positive organizational perspective. Additionally, this study is a reminder of the systemic nature of all living systems, such as schools, and the associated need to ensure well-being for all members of the learning community.